The Rise of Food & Beverages MSMEs During COVID-19 Pandemic in Tanjungpinang, Kepulauan Riau : A Motivational Perspective - Muhammad Rizki; Satriadi Satriadi; Eka Kurnia Saputra (Program MM Universitas Surabaya, 2023)
Abstract Purpose: This study aims to explore the entrepreneurial motivation behind food and beverage MSMEs in Tanjungpinang during the COVID-19 pandemic. Method: This study adopted a qualitative method. A total of 11 food and beverage MSMEs owners in Tanjungpinang that started their businesses in 2020 and 2021 were interviewed. Thematic analysis was used to analyze the data gathered. Result: The result of this study shows that financial rewards, independence, personal satisfaction, as well as the existence of opportunities as the driving forces behind a person’s decision to become an entrepreneur in the food and beverages industry in Tanjungpinang during the COVID-19 pandemic. This finding hopefully may give insight into the motivation behind an individual decision to become an entrepreneur in the food and beverages industry and why the number of food and beverages MSMEs is increasing.